Aspect retrieval in Hindi language feedback using Rule based method - Tiwari, Deepali Mishra (International Journal of Computer Sciences and Engineering, 2025)
The era of Web has resulted in generation of vast amount of user-generated content and analysis of all data by the viewer is time consuming process and viewers are interested towards the specific features of an entity, so the aspect based sentiment analysis became more important. Aspect term Extraction is the prime aim for the aspect based sentiment analysis. Aspect based sentiment Analysis have explored the rule based approach to extract the aspect term . By Experimented approach we have achieved average results for aspect term extraction.